Interwined study on brain bio-electrical signal and salivary protein for mental stress level indicator - Nur Aini Fadzilah Mohammad, 1990-, author 641770; Nugraha Priya Utama, supervisor 597188; Fakulti Biosains dan Kejuruteraan Perubatan 538915 (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2016)
Thesis (Sarjana Kejuruteraan (Bioperubatan))